The complete mitochondrial genome of Seniorwhitea reciproca (Diptera: Sarcophagidae). Issue 1 (2nd January 2019) - Ding, Zhiyu; Yang, Li; Shang, Yanjie; Ren, Lipin; Guo, Yadong; Chang, Yunfeng
Abstract: Seniorwhitea reciproca belongs to the Sarcophaga genus, Sarcophagidae family and Diptera order. Here, we report the complete mitochondrial genome of S. reciproca . The circular molecule is 15, 973 bp in length, consisting of A (39.80%), G (9.27%), T (36.44%), and C (14.49%), and it is composed of 22 tRNA genes, 13 protein-coding genes (PCGs), two rRNA genes, and a non-coding AT-rich region. 12 PCGs start with ATN, particularly, COI gene starting with TCG, and most PCGs use the typical stop codon TAA. Besides, the phylogenetic analyses upon mitogenomics would provide us further insights on the taxonomy and phylogeny of Sarcophagidae.